Cinnamaldehyde nanoemulsion decorated with rhamnolipid for inhibition of methicillin-resistant Staphylococcus aureus biofilm formation: in vitro and in vivo assessment - Lizi Yin; Yingzi Guo; Xiyuan Xv; Yuyun Dai; Luxin Li; Fengsheng Sun; Xue Lv; Gang Shu; Xiaoxia Liang; Changliang He; Zhiwen Xu; Ping Ouyang (Frontiers in Microbiology)
BackgroundStaphylococcus aureus (S. aureus) biofilm associated infections are prevalent and persistent, posing a serious threat to human health and causing significant economic losses in animal husbandry. Nanoemulsions demonstrate significant potential in the treatment of bacterial biofilm associated infections due to their unique physical, chemical and biological properties. In this study, a novel cinnamaldehyde nanoemulsion with the ability to penetrate biofilm structures and eliminate biofilms was developed.MethodsThe formulation of cinnamaldehyde nanoemulsion (Cin-NE) combined with rhamnolipid (RHL) was developed by self-assembly, and the efficacies of this formulation in inhibiting S. aureus biofilm associated infections were assessed through in vitro assays and in vivo experiments by a mouse skin wound healing model.ResultsThe particle size of the selected Cin-NE formulation was 13.66 ± 0.08 nm, and the Cin-RHL-NE formulation was 20.45 ± 0.25 nm. The selected Cin-RHL-NE formulation was stable at 4, 25, and 37°C. Furthermore, the Minimum Inhibitory Concentration (MIC) value of Cin-RHL-NE against MRSA was two-fold lower than drug solution. Confocal laser scanning microscopy (CLSM) revealed the superior efficacy of Cin-RHL-NE in eradicating MRSA biofilms while maintaining the Cin’s inherent functional properties. The efficacy of Cin-RHL-NE in the mouse skin wound healing model was superior to other formulation.ConclusionThese findings highlight the potential of the formulation Cin-RHL-NE for eradicating biofilms, and effective in treating notoriously persistent bacterial infections. The Cin-RHL-NE can used as a dosage form of Cin application to bacterial biofilm associated infections.